POLA KOMUNIKASI ORANGTUA DALAM MENGATASI KESULITAN BERKOMUNIKASI ANAK AUTIS (Studi Pada Orangtua Anak Autis Di Sekolah Dasar Swasta Khusus Autis Anak Mandiri Jalan Kutilang No. 5 Sukajadi Kota Pekanbaru) - ", Salman; Tinambunan, W. E. (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Today the symptoms of children with autism increasingly found. Autism has asense as the conditions experienced by a person which can affect the berhubunagn andcommunicate, especially in interpersonal communication. Autism is not a disease, butrather aimed at a genetic disorder that is associated with the development of the brainbefore, during, and even after birth.This study was conducted in an Sekolah Dasar Swasta Khusus Autis AnakMandiri Jalan Kutilang No. 5 Sukajadi Kota Pekanbaru. Subjects in this studyconsisted of teachers, parents, and students. While the object of research is the ParentCommunication Patterns in Autistic Children Communicate Overcoming Adversity(Studies in Autistic Children Parents in Sekolah Dasar Swasta Khusus Autis AnakMandiri Jalan Kutilang No. 5 Sukajadi Kota Pekanbaru.Holders important role in dealing with cases of autism, particularly in children,are the parents themselves. Parents are the ones who determine whether children withautism can develop properly or it gets worse. Parents are encouraged to think two timesmore astute in dealing with children with autism.Methods This study used a descriptive method with data collection interview.Therefore, it will be obtained a picture of the interpersonal communication betweenchildren with autism with parents.This study resulted in the conclusion that, parents who have children withautism experience many obstacles in her life dealing with autism. Parents havedifficulty in communicating both verbally and non-verbally, as well as interpersonalcommunication. Therefore, the role and support of parents is necessary in dealing withchildren with autism and the key word is merely a consequence.Keyword : Parents who have children with autism,Autism, Helping Autism.